Crystal structure of bucain, a three-fingered toxin from the venom of the Malayan krait (Bungarus candidus) - Murakami, M. T. [UNESP]; Kini, R. M.; Arni, R. K. [UNESP] (Bentham Science Publishers, 2009)
Bucain, a potent neurotoxin isolated from the venom of the Malayan krait (Bungarus candidus), induces paralysis and death. Its crystal structure has been determined at 2.10 Å resolution and based on the molecular topology and hydrophobicity profile is structurally classified as a three-fingered a-neurotoxin possessing a positively charged AChR-binding site. © 2009 Bentham Science Publishers Ltd.
Keywords: Bucain; Bungarus candidus; Crystal structure; Three-finger α-neurotoxin